Stabile Supply-Chains - Basierend auf der Theorie der Matching-Märkte - N, N

Die Berechnung von Machtindizes - ein Vergleich verschiedener Verfahren - N, N

Intermediaries in Buyer Seller Networks - N, N

Staatliche Regulierung in vertikal verbundenen Industrien - eine spieltheoretische Analyse - N, N

Pricing and Revenue Sharing of Bundles Using Game Theoretical Concepts - N, N

Paul Maar. Bielefelder Poet in Residence 2015 / Paderborner Kinderliteraturtage 2016

Philosophinnen in der Schule - Hagengruber, Ruth (Ethik/Philosophie Didaktik. Praxishandbuch für die Sekundarstufe I und II)

The Long-Lasting Tradition of Women Philosophers as an Insight into the History of Ideas - Hagengruber, Ruth Edith (Materials of the Inter-University Scientific Conference with International Participation)

Augenscheinlich und ohrenkundig. Bilderbuch-Hörspiel-Medienverbünde und ihr intermediales Potenzial für ästhetisches Lernen - Kruse, Iris (Im Bildungsfokus. Bilderbuchforschungsrezeption)

Kinderliterarische Medienverbünde im inklusiven Literaturunterricht der Grundschule - Mediale Darstellungsvielfalt als Chance für gemeinsame literarästhetische Erfahrungen - Kruse, Iris (Der inklusive Blick. Die Literaturdidaktik und ein neues Paradigma)

Gut vorbereitet in eine Autorenbegegnung - Kinder aus Paderborner Grundschulklassen befragen Paul Maar - Kruse, Iris (Paul Maar. Bielefelder Poet in Residence 2015 / Paderborner Kinderliteraturtage 2016)

Ästhetische Erfahrung, Sprachbildung und Teilhabe. Grundschulunterricht Deutsch

Ästhetisches Lernen, Sprachbildung und Teilhabe. Ästhetische Objekte als Lerngegenstände im inklusiven Unterricht. Basisartikel - Kruse, Iris (Grundschulunterricht Deutsch)

Intermedial und inklusiv. Ein kinderliterarischer Medienverbund stiftet gemeinsame literarische Erfahrungen - Kruse, Iris (Grundschulunterricht Deutsch)

Reconstruction of three-dimensional turned shaft surfaces with fractal functions - Thielen, Stefan; Magyar, Balázs; Piros, Attila (Tribology International)
A method for the reconstruction of turned shaft surfaces with a (fractal) Weierstrass–Mandelbrot-function (WMF) is presented. The WMF is modified to allow to freely choose a phase-shift for every frequency. The reconstruction is based on distinct profiles in axial and tangential direction and the statistical distribution of low-wavelength portions of the surface is taken into account by adding t-distributed random deviations to the surface. The work is validated by reconstructing measured shaft surfaces with different manufacturing parameters, which shows good accuracy for periodic surfaces. This method allows for a characterization of surfaces with a limited number of parameters and can be used to store the characteristics of measured surfaces with a reduced amount of data compared to a point-cloud surface.
Keywords: Roughness; Structure; Fractal; Machining

Lernprozesse verstehen und begleiten: Möglichkeiten der Förderdiagnostik im Kontext von Inklusion - Albers, Timm; Ritter, Charlotte Eva (Fördermagazin Grundschule)

Kinder mit Fluchterfahrungen in Kita und Grundschule - Albers, Timm; Ritter, Charlotte Eva (KiTa Fachtexte)

On the weakly competitive case in a two-species chemotaxis model - Black, Tobias; Lankeit, Johannes; Mizukami, Masaaki (IMA Journal of Applied Mathematics)
Keywords: Applied Mathematics

Boundedness in a Keller–Segel system with external signal production - Black, Tobias (Journal of Mathematical Analysis and Applications)
Keywords: Applied Mathematics; Analysis

Blow-up of weak solutions to a chemotaxis system under influence of an external chemoattractant - Black, Tobias (Nonlinearity)
Keywords: Applied Mathematics; General Physics and Astronomy; Mathematical Physics; Statistical and Nonlinear Physics